Labour Market Regulation, Productivity-Improving R&D and Endogenous Growth - Tapio Palokangas (Institute for the Study of Labor (IZA), 2003)
We present a growth model in which R&D increases productivity, union-firm bargaining determines the distribution of rents and the government can support unions by labour market regulation. We show that if unions are initially very strong, regulation increases only the workers? profit share and has no impact on employment and growth. Otherwise, regulation increases wages. Because firms try to escape this cost increase through the improvement of productivity by R&D, the economy grows faster. Regulation (deregulation) is desirable when the growth rate is below (above) some critical level.
Keywords: J50; O40; 330; endogenous growth; labour unions; regulation; Neue Wachstumstheorie; Lohnverhandlungstheorie; Gewerkschaftlicher Organisationsgrad; Arbeitsrecht; Industrielle Forschung; Produktivität; Theorie